Experimental evaluation of maximum debonding strain in thick CFRP layers for flexural strengthening - Do, Khang Viet (My University, 2025)
Carbon fiber reinforced polymer (CFRP) is widely used for strengthening RC structures; however, the externally bonded reinforcement (EBR) method is often governed by premature debonding at the CFRP-concrete interface, preventing CFRP from reaching its full tensile capacity. Current design provisions limit the effective strain to control debonding, but most are based on test results conducted using thin CFRP layers, leaving uncertainties in their applicability to thick CFRP systems. This study investigated the maximum debonding strain, load-carrying capacity, and failure behavior of RC T-beams strengthened with multiple layers of thick CFRP sheets (V-Wrap C400HM) using the epoxy resin V-Wrap 770. The experimental program included ten RC T-beams, which were divided into two groups: low-strength concrete (2.86 ksi) and normal strength concrete (4.44 ksi). Each group included a control beam, three beams strengthened with one to three thick CFRP layers, and one hybrid beam using an externally bonded reinforcement on grooves (EBROG) technique, where the soffit was pre-grooved and filled with epoxy putty before applying one thick CFRP layer. All specimen were tested under four-point bending, using displacement – controlled loading at a constant rate of 0.05 in/min. Experimental results showed significant strength enhancement with CFRP, with the peak performance observed in the two-layer systems, which provided the best strength – ductility balance. Specimens with three CFRP layers exhibited premature debonding or cover delamination, indicating a practical limit for effective CFRP thickness without additional mechanical anchorage. The hybrid grooved-putty configuration improved bond performance when applied in the normal strength concrete series compared to a single-layer externally bonded system. Among evaluated design guidelines, ACI 440.2R-23 provided most reliable prediction as compared to TR55, CNR-DT 200, fib-14, and JSCE
Keywords: Thick CFRP; Strengthening; Flexural; Experimental